Social media effects on perceptions of graduate students' entrepreneurial intentions - Ifrah Laiq (Journal of Enterprise and Development (JED), 2021)
The main purpose of this research is to study the impact of perceived desirability and perceived feasibility on entrepreneurial intentions and also identify the difference in intentions of gender and the moderating impact of social media. For this quantitative research, a study survey was conducted in March 2021 in the universities of Pakistan. The target sample for the study was 500 including both male and female graduate students. The results of the study reveal the positive impact of perceived desirability and feasibility on entrepreneurial intentions. Both males and females are ambitious to start their own entrepreneurial ventures but there is a difference in intentions and the direct influence of social media is identified. The study is limited by its cross-sectional data and it is difficult to inspect the business intentions because such intentions are developed inside the people’s minds. It holds important implications for policymakers and educators to enhance self-efficacy and outcome expectations. The research took all three approaches of entrepreneurship into account for exploring the positive relation between perceptions and entrepreneurial intentions. By incorporation of social media variables into the study framework, it focuses on issues not presently discussed in the entrepreneurial literature. For future research, the study would suggest exploring the moderating role of other sociological and personal characteristics. The attitude of both genders toward entrepreneurship has remarkably changed and this independency because of social media can give them a better understanding of the practical world.